Correlation of Iodine content of mother’s milk and urine with their child’s TSH level - Singh, Shruti; Lamsal, Madhab; Baral, Nirmal; Bhatta, Nisha Keshary; Uprety, Dhruba K (Asian Journal of Medical Sciences, 2015)
Background: Iodine deficiency is still a significant public health problem. In the rural plains of Nepal, it remains a mild-to-moderate public health problem among pregnant and lactating women despite the availability of iodized salt. To date, only limited attention has been paid to breast-milk iodine content despite its importance in the intellectual development of infants. Objectives: (i) To determine iodine content in mother’s urine, mother’s milk and to measure their respective child’s TSH level. (ii) To correlate iodine content of mother’s urine with child’s TSH level and also mother’s milk content with child’s TSH level. Setting and Design: cross sectional study in human using consecutive sampling technique Materials and Methods: Mother’s urinary and milk iodine level was measured by Ammonium Persulfate Digestion Microplate method using Sandell-Kolthoff reaction in a sealing cassette (Hitachi, Japan) and child’s TSH by ELISA commercial Kit from Eliscan (RFCL, India) based on classical sandwich technique. Statistical analysis used: Spearman’s correlation was performed in quantitative variables. A p-value less than 0.05 and 0.001 were considered statistically significant and highly significant respectively Results: The median mother’s urine was 174.96 µg/L(97.39-215.43) and their respective median child TSH level was 3.86 mIU/L(2.66-4.80). Median mother’s milk iodine was 129.90 µg/L (94.14-165.94).There was significant negative correlation between mothers’ urinary iodine content and their child’s TSH (r2= -0.391, p = 0.005) and between mother’s urinary iodine and their child’s TSH (r2= -0.471, p = 0.001). There was positive correlation between mother’s milk iodine and mother urinary iodine but not statistically significant ((r2= 0.261, p = 0.067). Conclusion: Mothers urinary iodine, mother’s milk iodine and child TSH are interrelated with each other. Asian Journal of Medical Sciences Vol.7(1) 2015 40-48